Comparison of MRI and high‐resolution transvaginal sonography for the local staging of cervical cancer. Issue 2 (21st August 2015) - Moloney, Fiachra; Ryan, David; Twomey, Maria; Hewitt, Matt; Barry, Josephine
ABSTRACT: Purpose: The aim of this prospective study was to compare the diagnostic accuracy of transvaginal sonography (TVS) with that of MRI in the local staging of cervical cancer. Methods: All consecutive patients diagnosed with invasive carcinoma of the cervix over a 3‐year period underwent MRI of the pelvis and TVS according to a standardized protocol. Results: In total, 46 patients were recruited to the study. We found a strong correlation between MRI and TVS in the assessment of tumor volume in both early‐stage and advanced‐stage disease ( p < 0.0001). Both MRI and TVS had a sensitivity of 80%, a specificity of 50%, and a diagnostic accuracy of 63.6% for the detection of stromal invasion in early‐stage disease. For the detection of parametrial invasion, we found sensitivity rates of 40% for MRI and 86% for TVS; specificity rates of 78.8% for MRI and 20% for TVS; and diagnostic accuracy rates of 89% for MRI and 78.7% for TVS. A matched‐sample analysis revealed that there was no statistically significant difference between MRI and TVS in the assessment of stromal or parametrial invasion ( p = 0.06). Conclusions: TVS performed by a dedicated gynecologic radiologist is a feasible and economic imaging modality with a diagnostic accuracy comparable to that of MRI. It may be used as an adjunct to MRI for the local staging of invasive cervical cancer or to allow for rapid and confident triage of patients into operative and nonoperative categories for management in the gynecologic outpatient setting. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound 44:78–84, 2016